Pelaksanaan Pengadaan Barang dan Jasa Melalui E-Katalog terhadap UMKM - Khumaira, Sitria Amalia (Prosiding, 2024)
The purpose of this study is to analyze the implementation of e-catalogs in the procurement of government goods/services and to examine the effect of e-catalog implementation in the procurement of goods and services. As Indonesia's economy grows and develops, the government needs more governance. When these needs are met through the purchase of goods or services. The need for goods and services is the most important part of governance. Electronic procurement services are information technology management services to facilitate the implementation of electronic procurement of goods / services (Presidential Regulation No.12 of 2021 article 1 point 21). Electronic procurement transactions can be carried out between business organizations and other businesses, business organizations and consumers or government organizations and businesses as providers. The policy on the procurement of goods / services through an e-purchasing mechanism with an electronic catalog system (E-catalog) is a new policy that aims to support the government procurement process in the Internet of Things (IoT) era to be in line with the times. The research method used is normative juridical. The benefit of using e-catalogs is that clients and labor suppliers can both know the progress of the sales made. This is one form of implementation transparency. E-catalog procurement will provide benefits to the establishment of the principles of good governance, namely accountability and transparency, so as to encourage the public administration reform movement. Providers in E-Purchasing itself can be followed by all providers of goods / services that meet the requirements in accordance with the selection method, including MSMEs which can also participate as providers which are a form of government efforts for economic equality including the regional economy.